Group B streptococcus neonatal invasive infections, France 2007–2012. (October 2015) - Joubrel, C.; Tazi, A.; Six, A.; Dmytruk, N.; Touak, G.; Bidet, P.; Raymond, J.; Trieu Cuot, P.; Fouet, A.; Kernéis, S.; Poyart, C.
Abstract: Streptococcus agalactiae (group B streptococcus (GBS)) is the leading cause of invasive infections among newborns in industrialized countries, with two described syndromes: early-onset disease (EOD) and late-onset disease (LOD). Since the introduction in many countries of intrapartum antibioprophylaxis (IAP), the incidence of EOD has dramatically decreased, whereas that of LOD remains unchanged. We describe the clinical and bacteriological characteristics of 438 GBS neonatal invasive infections notified to the French National Reference Centre for Streptococci in France from 2007 to 2012. Clinical data were retrieved from hospitalization reports or questionnaires. Capsular type, assignment to the hypervirulent clonal complex (CC)17 and antibiotic susceptibility profiles were determined. One hundred and seventy-four (39.7%) and 264 (60.3%) isolates were responsible for EOD, including death in utero, and LOD, respectively. EOD was associated with bacteraemia ( n  = 103, 61%) and LOD with meningitis ( n  = 145, 55%). EOD was mainly due to capsular polysaccharide (CPS) III isolates ( n  = 99, 57%) and CPS Ia isolates ( n  = 40, 23%), and CPS III isolates were responsible for 80% ( n  = 211) of LOD cases. CC17 accounted for 80% ( n  = 121) of CPS III isolates responsible for meningitis ( n  = 151; total cases of meningitis, 188). Bad outcome risk factors were low gestational age and low birthweight. LOD represents almost 60% of cases of neonatal GBS disease in France and other countries in which IAP has been implemented. This observation reinforces the need to develop new prevention strategies targeting CC17, which is predominant in GBS neonatal infections.